A Comparison of Quality-of-Life Domains and Clinical Factors in Ovarian Cancer Patients: A Gynecologic Oncology Group Study - von Gruenigen, Vivian E. (2010)
CONTEXT: Women diagnosed with ovarian cancer are at risk for reduced quality of life (QOL). It is imperative to further define these declines to interpret treatment outcomes and design appropriate clinical interventions. OBJECTIVES: The primary objective of this study was to compare data obtained from ovarian cancer patients with normative data to assess the degree to which QOL differs from the norm. Secondary objectives were to examine demographic variables and determine if there was a correlation between physical/functional and social/emotional scores during chemotherapy. METHODS: Patients with Stage III/IV ovarian cancer on Gynecologic Oncology Group Protocols 152 and 172 who underwent surgery followed by intravenous paclitaxel and cisplatin completed the Functional Assessment of Cancer Therapy-Ovarian. The Functional Assessment of Cancer Therapy scale includes the four domains of physical, functional, social, and emotional well-being (PWB, FWB, SWB, and EWB, respectively). RESULTS: Ovarian cancer patients had a total QOL (Functional Assessment of Cancer Therapy-General) score similar to the U.S. female adult population. However, the reported subscale scores were 2.0 points (95% confidence interval [CI] 1.4–2.5, P < 0.001, effect size = 0.37) lower in PWB, 0.9 points (95% CI 0.3–1.5, P = 0.005, effect size = 0.13) lower in FWB, 5.0 points (95% CI 4.6–5.3, P < 0.001, effect size = 0.74) higher in SWB, and 0.8 points (95% CI 0.3–1.2, P < 0.001, effect size = 0.16) lower in EWB. Correlation between the sum of PWB and FWB and the sum of SWB and EWB was r = 0.53 (P < 0.001). Age was positively correlated with EWB (r = 0.193; 95% CI 0.09–0.29). CONCLUSION: Ovarian cancer patients have decreased QOL in physical, functional, and emotional domains; however, they may compensate with increased social support. At the time of diagnosis and treatment, patients’ QOL is affected by inherent characteristics. Assessment of treatment outcomes should take into account the effect of these independent variables.